2011
DOI: 10.1016/j.socscimed.2011.06.031
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social networks and pathways to kidney transplant parity: Evidence from black Americans in Chicago

Abstract: Research has shown that black dialysis patients in the United States are significantly less likely than their white peers to be evaluated and listed for a kidney transplant. Extrapolating from social network theory, I hypothesize that a lack of access to social contacts with information about kidney transplantation may hinder information transaction regarding the benefits of, and pathway to, transplantation. In 2007–2008, the following research questions were addressed in an investigation in Chicago, USA: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
2
36
2
2
Order By: Relevance
“…Weakly linked networks are characteristic of advice and expert networks, and the person in the center is the most influential. Whereas we found that patients in strongly interlinked networks completed more steps toward kidney transplantation, other studies found that patients in these networks were misinformed and failed to complete the steps (9). Whereas we found that patients in strongly interlinked networks completed more steps toward kidney transplantation, other studies found that patients in these networks were misinformed and failed to complete the steps (9).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Weakly linked networks are characteristic of advice and expert networks, and the person in the center is the most influential. Whereas we found that patients in strongly interlinked networks completed more steps toward kidney transplantation, other studies found that patients in these networks were misinformed and failed to complete the steps (9). Whereas we found that patients in strongly interlinked networks completed more steps toward kidney transplantation, other studies found that patients in these networks were misinformed and failed to complete the steps (9).…”
Section: Discussioncontrasting
confidence: 70%
“…First, in-center hemodialysis is the predominant treatment for end-stage renal disease (ESRD) in the United States (19). Little is known about the function and structure of hemodialysis patient social networks (6)(7)(8)(9); however, research examining the social support and information provided by clinic staff and other patients (21)(22)(23)(24)(25)(26) highlights the importance of social networks within the hemodialysis clinic. Little is known about the function and structure of hemodialysis patient social networks (6)(7)(8)(9); however, research examining the social support and information provided by clinic staff and other patients (21)(22)(23)(24)(25)(26) highlights the importance of social networks within the hemodialysis clinic.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the barriers that may have prevented patients from getting a transplant had they been medically suitable, we deliberately included patients who may have been unsuitable for transplant. Moreover, their attitudes may have influenced others who were medically suitable (17)(18)(19). Severe PVD is a relative contra-indication to transplantation at our center and a known predictor of morbidity and mortality in ESRD (29), which may explain why these patients were less likely to want LDKT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all patients were eligible to participate in the study, regardless of their candidacy for kidney transplantation. We reasoned that the concerns and attitudes of both potentially eligible and ineligible LDKT candidates might help us develop targeted interventions designed to increase LDKT rates among black women and alleviate some existing disparities (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that a majority of dialysis patients [71.6% (11)- 94% (12)] are interested in getting a KTx. In our study, only 19% of the dialysis professionals completing this survey thought that >50% of their patients were interested in KTx.…”
Section: Discussionmentioning
confidence: 99%